Methods of program analysis of high-resolution electrocardiogram recorded using hardware-software complex based on nanosensors - M. L. Ivanov; D. K. Avdeeva; М. М. Yuzhakov; S. А. Rybalka; Guo Wenjia; I. V. Maksimov; M. V. Balakhonova (Омский научный вестник)
The paper aims to consider the software methods used for detection of elements of high-resolution electrocardiographic (ECG) signals recorded using a nanosensor-based hardware and software complex. To achieve the aim, the study employed the following methods: correlation analysis, bi-directional filtering, first-order derivative, and correction algorithms. For cases when the automatic detection of elements was made with an error, an additional algorithm for manual correction of QRS elements has been developed.